Association of Circulating Vitamin E (α- and γ-Tocopherol) Levels with Gallstone Disease - Waniek, Sabina (Nutrients, 2018)
In addition to well-established risk factors like older age, female gender, and adiposity, oxidative stress may play a role in the pathophysiology of gallstone disease. Since vitamin E exerts important anti-oxidative functions, we hypothesized that circulating vitamin E levels might be inversely associated with prevalence of gallstone disease. In a cross-sectional study, we measured plasma levels of α- and γ-tocopherol using high performance liquid chromatography in a community-based sample (582 individuals; median age 62 years; 38.5% women). Gallstone disease status was assessed by ultrasound. Multivariable-adjusted logistic regression models were used to estimate the association of circulating α- and γ-tocopherol/cholesterol ratio levels with prevalent gallstone disease. Lower probabilities of having gallstone disease were observed in the top (compared to the bottom) tertile of the plasma α-tocopherol/cholesterol ratio in multivariable-adjusted models (OR (Odds Ratio): 0.31; 95% CI (Confidence Interval): 0.13–0.76). A lower probability of having gallstone disease was also observed for the γ-tocopherol/cholesterol ratio, though the association did not reach statistical significance (OR: 0.77; 95% CI: 0.35–1.69 for 3rd vs 1st tertile). In conclusion, our observations are consistent with the concept that higher vitamin E levels might protect from gallstone disease, a premise that needs to be further addressed in longitudinal studies.